Belgium’s Extrajudicial Recovery of Uncontested Money Debts: Can an Extension to Consumer Debt be Envisaged? - van Doninck, Jachin; Davidts, Justine (Revista Ítalo-Española de Derecho Procesal, 2025)
Consumer debt is a pervasive issue that imperils both debtors and their creditors. Belgium has in the past created an out-of-court gateway for creditors to recover debt in business to business relationships. Discussions on whether to extend that scheme to consumer debt are ongoing. European Union law and the case law of the European Court of Justice on consumer protection should be taken into account in devising such scheme but are not an insurmountable obstacle. Belgium could prove an innovative testing ground for similar schemes elsewhere.